EFEKTIVITAS PENGELOLAAN KEUANGAN DESA: STUDI PADA PEMERINTAHAN DESA DI KOTA SAWAHLUNTO - Mulyadi, Irma (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted to analyze the effectiveness of village financial management in the Village Government in Sawahlunto City and the factors that influence it. The method used by researchers in analyzing the results of this study is to use a descriptive analysis method. The data used in this study are primary and secondary data from the Very Disadvantaged Villages, Disadvantaged Villages and Developing Villages. The results of this study indicate that the process of compiling village planning and designation as stipulated in the Village RPJM and RKPDesa refers to Minister Regulation No. 114 of 2014 and village financial management that refers to Permendagri Number 113 of 2014 and Sawahlunto Mayor Regulation regarding the amount of the village budget. The effectiveness of the absorption of village funds obtained from the results of this study shows the level of achievement of the realization of village finances reached 97.22% -100%. The factors that influence the effectiveness of village financial management are the quality of human resources, technology utilization, internal control systems, village financial supervision, and community participation.